2022
DOI: 10.1186/s13072-022-00469-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of variant subunits and associated factors to genome-wide distribution and dynamics of cohesin

Abstract: Background The cohesin complex organizes the genome-forming dynamic chromatin loops that impact on all DNA-mediated processes. There are two different cohesin complexes in vertebrate somatic cells, carrying the STAG1 or STAG2 subunit, and two versions of the regulatory subunit PDS5, PDS5A and PDS5B. Mice deficient for any of the variant subunits are embryonic lethal, which indicates that they are not functionally redundant. However, their specific behavior at the molecular level is not fully un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Which molecular mechanisms could link enhancer activity and connectivity? The cohesin complex, and particularly its isoform containing the STAG2 subinit, is known to be recruited to active enhancers, including those that do not bind CTCF 85,86 . This recruitment could be directly impacted by genetic aberrations in enhancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Which molecular mechanisms could link enhancer activity and connectivity? The cohesin complex, and particularly its isoform containing the STAG2 subinit, is known to be recruited to active enhancers, including those that do not bind CTCF 85,86 . This recruitment could be directly impacted by genetic aberrations in enhancer activity.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse models harbouring mutations in both the genes have shown a lower leucocyte count and an increased granulocyte/monocyte fraction along with a decrease in hemoglobin levels. It was observed that there was an increase in their hematopoietic stem and progenitor cells thus indicating a higher self-renewal capacity in them ( Cuadrado et al, 2022) . This study highlights the importance of mouse models to study clonal hierarchy and their co-operativity in MDS and its aetiology ( Figure 2 ).…”
Section: Phenotypic Insights From Modelling Cohesin Loss Of Function ...mentioning
confidence: 99%
“…Cohesin mutations have also been shown to reduce overall chromatin accessibility while increasing accessibility for specific transcription factor motifs related to HSC self-renewal, such as ERG1, GATA2, and RUNX1 ( Mazumdar et al, 2015 ). Studies which aimed to study how STAG1 and STAG2 cohesin subunits are distributed throughout the genome also showed that non-CTCF cohesin binding sites are bound by cohesin-STAG2 ( Cuadrado et al, 2022 ). This is further proof of STAG2 having a specialised function in myeloid malignancies.…”
Section: Cohesin Mutations Drive Myeloid Malignancies Through Changes...mentioning
confidence: 99%
“…In vitro, NIPBL is also required both for topological entrapment of plasmid DNA and for loop extrusion by cohesin [20][21][22] . PDS5 proteins compete with NIPBL for binding cohesin and are, together with WAPL, required for cohesin unloading [23][24][25][26] . Thus, NIPBL-bound, presumably loop extruding cohesin, cannot be unloaded.…”
mentioning
confidence: 99%